Research on Interdisciplinary Collaborative Teaching in Cultural Industry Management - Dong , Shu (Transactions on Social Science, Education and Humanities Research, 2024)
Cultural industry management is a profession that cultivates composite talents who understand both culture and management with the rise and development of China’s cultural industry. Based on the analysis of the interdisciplinary characteristics of this major, this article takes Shangluo University as an example to study the shortcomings of talent cultivation in the field of cultural industry management. It proposes measures to optimize talent cultivation in the field of cultural industry management from the aspects of curriculum design, faculty construction, system optimization, and resource sharing, in order to improve the quality and efficiency of talent cultivation in the field of cultural industry management. It provides a reference for improving the practical teaching of cultural industry management and helps to achieve the talent cultivation goals that serve the construction of cultural industries and local economic development.